Hybrid and nonhybrid laminate composites of sugar palm and glass fibre-reinforced polypropylene: effect of alkali and sodium bicarbonate treatments - Isma'ila, Mukhtar; Leman, Zulkiflle; Zainudin, Edi Syams; Ishak, Mohamad Ridzwan (Hindawi Limited, 2019)
In recent years, the hybrid composites of cellulosic and synthetic fibres are tailored to yield materials with reduced cost and weight. Prior to the fabrication of the hybrid composite, in most case, the cellulosic fibre needs surface modification for proper bonding. Therefore, this study investigates the effect of sodium bicarbonate treatment on the physical and mechanical properties of the hybrid and nonhybrid laminate composites of sugar palm and glass fibre-reinforced polypropylene. The findings will be compared with the conventional alkali treatment. The laminate composites were fabricated using the film stacking technique and hot compression process. Prior to the fabrication process, the sugar palm fibre in it which is naturally woven mat was treated with 4 wt% and 10 wt% alkali and sodium bicarbonate, respectively. All the laminate composites were investigated by tensile, flexural, and impact test, water absorption, and morphological examination. The tensile strength increased with both alkaline and sodium bicarbonate treatments for the hybrid and nonhybrid composites. The increase was more pronounced with the alkaline-treated SPF composite (L03) which displayed the highest value of 61.75 MPa, while that of the sodium bicarbonate-treated SPF composite (L04) recorded 58.76 MPa against 53.01 MPa for the untreated SPF composite (L02). The same trend was observed for the flexural strength. In overall, the alkaline treatment yielded better performance in comparison with sodium bicarbonate treatment.